Documenting the Impact of Infra Low Frequency Neurofeedback on Underserved Populations With Complex Clinical Presentations - Fleischman, Matthew J. (Frontiers in Human Neuroscience, 2022)
There is a crisis in mental health. The demand for services is huge; the efficacy of current services is lacking, and the traditional path to developing effective treatments is not working. This paper describes an approach based on implementing infra low frequency (ILF) neurofeedback in agencies that work with the underserved and collecting data on client’s concerns, behavior, quality of life and cognitive performance. We also track session-by-session changes in client concerns and their relation to ILF neurofeedback protocols. Results are reviewed for over 300 clients having been seen in such agencies. Limitations and future directions are discussed for this model.